Gemcitabine-Induced Pseudocellulitis in a Patient With Recurrent Lymphedema: A Case Report and Review of the Current Literature. (January 2016) - Curtis, Susanna; Hong, Simon; Gucalp, Rasim; Calvo, Manuela
Abstract : Gemcitabine is a chemotherapeutic agent used for treatment of a variety of malignancies. It has been associated with multiple cutaneous reactions including rash, alopecia, and pruritus. Less commonly, gemcitabine has been associated with "pseudocellulitis, " a noninfectious skin inflammatory reaction, which resembles cellulitis. The majority of cases reported in the literature are radiation recall reactions in which inflammation occurs in areas of previous radiation post drug treatment; however, there are also reports of pseudocellulitis occurring in areas of preexisting lymphedema. The pathophysiology of both of these reactions are still unknown, though it is theorized that areas of lymphedema may both increase concentration of gemcitabine and reduce its rate of metabolism leading to increased drug exposure time. In this study, we report a case of pseudocellulitis in a patient with chronic lower extremity lymphedema and a review of the current literature. By recognizing this side effect of gemcitabine, one can avoid unnecessary hospitalization and exposure to antibiotics.